ANALISIS SYSTEM USABILITY APLIKASI MOBILE JKN DALAM PELAYANAN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DI PROVINSI DKI JAKARTA - Simanjuntak, Jeremia Gom Gom Parulian; Harun, Jason (Kebijakan : Jurnal Ilmu Administrasi, 2026)
This study aims to evaluate the usability of the JKN mobile application in BPJS Health services using the System Usability Scale (SUS), focusing on three variables: effectiveness, efficiency, and user satisfaction, including both users and the application provider. The JKN mobile application has received several negative reviews regarding issues such as difficulty logging in, black screens, sudden application crashes, and other problems. Therefore, an evaluation is needed to gain a deeper understanding of the application’s usability. This research employs a quantitative approach with a descriptive survey method. Data collection was conducted through a questionnaire distributed to 384 users of the application and interviews with the application provider. The study uses the SUS theory developed by John Brooke (1986), consisting of 10 questionnaire items across the three variables. The results show that respondents perceive the JKN mobile application as effective, efficient, and satisfying for both users and the provider. This is indicated by the ease and benefits experienced by respondents in quickly understanding how to use the application, as well as its straightforward and uncomplicated nature. However, efforts are still needed to further improve the JKN mobile application, such as organizing seminars or webinars to educate the public on how to use the app and developing notification features to inform users about new features or usage tips. Improving the application’s usability is expected not only to enhance the user experience but also to contribute to the success and sustainability of the JKN program itself.